AQUAAEROBIC AS AN IMPORTANT DETERMINANT OF PHYSICAL ACTIVITY AMONG WOMEN - Kreft, P.; Skalski , D. W.; Mirska, I.; Kowalski, D.; Tsyhanovska, N.; Zarichańska, L. O. (Rehabilitation and Recreation, 2023)
The leitmotif in modern life is a greater awareness of the importance of sport and exercise in maintaining health and physical fitness. Doctors are increasingly emphasizing the importance of physical activity in the prevention of heart and circulatory system diseases. Maintaining an attractive appearance for many years depends, among other things, on physical activity. Exercises practiced systematically, rationally and consistently are a powerful stimulus for young people’s development, for adults a preventive and compensatory measure, and for the elderly they are a chance to postpone senile infirmity. More and more women realize that they should take care of their bodies not only for the sake of an attractive appearance, but also to function better on the mental and social level. Living in the modern world, despite many conveniences, requires special care to maintain health. There are various negative phenomena that threaten health, brought about by the development of civilization. A woman aware of the numerous benefits of an active lifestyle and a healthy, balanced diet is definitely more motivated to consistently take actions that bring results in the form of a shapely figure, improvement of health and well-being. It is very important to start instilling the ideas of a healthy and active lifestyle in childhood, when positive patterns and habits begin to form in a young person. Contemporary fashion, promoting a slim and athletic figure as the ideal of beauty, stimulates many women to take up physical activity. Youth, attractive appearance, health have always been an indicator of success in many areas of life – professional and personal. The goals guiding a woman who decides to change her lifestyle to a healthier and more active one are important for her commitment and consistent actions. Physical exercise and physical activity maintain the efficiency of individual body functions until old age. They develop the ability to perform various life activities, including physical work, and facilitate the adaptation of the body to the conditions of professional work and everyday life. Aqua aerobic exercises have a positive effect on the skeletal system, change in muscle tension, the influence of hormonal factors, change in the excitability of the vegetative system, stimulation of the centers responsible for regulating the circulatory system and mental condition. Thanks to physical activity, we can effectively learn, work and function properly in society.